Cu2+ reduces hemolytic activity of the antimicrobial peptide HMPI and enhances its trypsin resistance. (5th May 2020) - Peng, Jinxiu; Yang, Yang; Zhao, Ping; Qiu, Shuai; Jia, Fengjing; Wang, Jiayi; Liang, Xiaolei; Chaudhry, Ahmed Shabbir; Xu, Peihan; Yan, Wenjin; Xu, Zhaoqing; Wang, Kairong
Abstract: Nowadays, drug-resistant microbes are becoming a serious clinical problem threatening people's health and life. Antimicrobial peptides (AMPs) are believed to be potential alternatives of conventional antibiotics to combat the threat of drug-resistant microbes. However, the susceptibility of AMPs toward proteases is one of the major problems limiting their clinical use. In the present study, we reported the effect of Cu 2+ on the bioactivity of AMP HMPI. We found that the addition of Cu 2+ could improve the protease resistance of AMP HMPI without affecting its bioactivity. Notably, after the binding of Cu 2+ with HMPI, the hemolytic activity of HMPI was greatly decreased. In addition, our results also demonstrated that the addition of Cu 2+ increased the production of reactive oxygen species in the fungal cells, which may be a supplement for the antifungal activity of HMPI. In conclusion, the introduction of Cu 2+ may provide an inorganic strategy to improve the stability and decrease the hemolytic activity of AMP HMPI, while maintaining its antifungal activity.